2012
DOI: 10.1073/pnas.1206945109
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine desulfurase Nfs1 and Pim1 protease control levels of Isu, the Fe-S cluster biogenesis scaffold

Abstract: Fe-S clusters are critical prosthetic groups for proteins involved in various critical biological processes. Before being transferred to recipient apo-proteins, Fe-S clusters are assembled on the highly conserved scaffold protein Isu, the abundance of which is regulated posttranslationally on disruption of the cluster biogenesis system. Here we report that Isu is degraded by the Lon-type AAA+ ATPase protease of the mitochondrial matrix, Pim1. Nfs1, the cysteine desulfurase responsible for providing sulfur for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…We conclude that residues Leu 479 and Met 482 of Nfs1 are critical for interaction with Isu1. This conclusion is in accord with data indicating the importance of the C-terminal segment of both Nfs1 (46) and its E. coli ortholog (7) for interaction with the scaffold. We note that it is likely that residues in addition to Leu 479 and Met 482 play important roles in the interaction of Nfs1 with Isu1.…”
supporting
confidence: 91%
“…We conclude that residues Leu 479 and Met 482 of Nfs1 are critical for interaction with Isu1. This conclusion is in accord with data indicating the importance of the C-terminal segment of both Nfs1 (46) and its E. coli ortholog (7) for interaction with the scaffold. We note that it is likely that residues in addition to Leu 479 and Met 482 play important roles in the interaction of Nfs1 with Isu1.…”
supporting
confidence: 91%
“…A plausible reason for the decrease in the Nfs1 levels could be attributed to its relatively lower stability due to the compromised ISD11 interaction, causing aggregation and degradation by proteases in the mitochondrial compartment. Such regulatory mechanisms have been demonstrated in yeast Isu1 mutants, which are defective in the Nfs1 interaction and undergo degradation by Pim1 protease, therefore, modulating the protein levels (18). In addition to reduced Nfs1 expression, diminished levels of Isu1 was also observed in mutant strains, especially with a stronger ts phenotype and R68A disease variant, implying the paramount nature of these residues for maintaining Isu1 levels as well.…”
Section: Discussionmentioning
confidence: 89%
“…In bacteria, the crystal structure of the NFS1 ortholog IscS shows that it forms a tight complex with IscU, thereby accelerating sulfur transfer from IscS to IscU (16,17). Biochemical and genetic analysis involving yeast Nfs1 showed that it stabilizes the scaffold protein Isu1 and modulates its level in different growth conditions (18). Moreover, both Nfs1 and Jac1 exhibit binding to mutually exclusive sites in Isu1 (19).…”
mentioning
confidence: 99%
“…A recent study demonstrated that apo-ISCU (Isu) in yeast cells is rapidly degraded by the Lon-type AAAϩ protease Pim1 (46). If human ISCU is similarly degraded when it lacks an Fe-S cluster, then oxidant-mediated cluster dissolution would lead to a decreased protein half-life, an effect seen in several other FIGURE 6.…”
Section: Oxidative Stress Exacerbates the Phenotype Of Impaired Fe-s mentioning
confidence: 99%